Silicon self-assembled nanodots fabricated using a radio-frequency magnetron sputtering method - Lim, Qiao Jie (2008)
Silicon nanodot is a promising nanostructured material for future single-electron devices in nanoelectronic system. The self-assembly growth of silicon nanodots on sapphire substrate was investigated, with highlights on the very early stage of nucleation and the growth process. The scope of study covers both the theoretical approach and experimental works. A classical theory of nucleation was applied to a liquid-solid phase transition, combined with high temperature supercooling to establish the expression for the net energy change in the formation of silicon nanodots. Using a computer program, the predicted parameters, such as critical radius (r*), critical energy (?G*), surface energy (?NS), and free energy change per unit area (?Gv) were obtained and tabulated into a dome-like shape nucleus following the Volmer-Weber growth mode. Experimental works have been conducted using a radio-frequency magnetron sputtering under the varying conditions of 5-20 minutes deposition time, 100-400°C substrate temperature and 50-200 W radio-frequency power. Optimum experimental conditions for the onset of silicon nanodot were found to be at 5 minutes/400 oC/100 W setting. Characterization measurements have been done on this sample using AFM, PL, XRD and EDX. Observation from AFM indicated the presence of small islands with an average diameter of 40.81 nm. The results from PL analysis revealed the existence of a peak which corresponded to a bandgap energy of 1.78 eV. This was further confirmed by the presence of 0.48 at.% of silicon on the substrate using EDX. A further XRD analysis gave no indication of a crystallinity phase probably due to extremely small amount of silicon formed on the substrate. The results showed that the formation of dome-like silicon nanodots on sapphire substrate occurred during the first 3 minutes of deposition, ascribed by the surface energy mismatch at interface and governed by a Volmer-Weber growth mode. A further growth of silicon nanodots were found to change their properties and strongly dependent on the experimental conditions.